The effects of Hip Abductor Fatigue on Low Back Pain Development during Prolonged Standing - Viggiani, Daniel (University of Waterloo, 2015)
The goal of this thesis was to use hip abductor fatigue to perturb those who do and do not develop pain from standing and determine changes in muscular and postural responses. Forty young healthy participants performed two sessions of standing work for two hours each. Participants performed a side-lying leg raising exercise to fatigue prior to one of the standing sessions, the other session acted as a control. Surface electromyography (EMG) of six muscles bilaterally, motion capture of the trunk and lower limbs, and force plate data under each foot were measured continuously during each standing session. Self-reported pain and isometric hip abductor strength were assessed at discrete time points using 100 mm visual analog scales and uni-axial force transducers respectively. Participants were classified as pain developers (PDs) or non-pain developers (NPDs) based on a 10 mm threshold in low back pain scores during the control session. PDs (16/40) reported decreases in low back pain while standing during the fatigue session (10.9 ± 11.7 mm reduction) while NPDs reported minimal changes in pain with fatigue (1.5 ± 3.9 mm increase). Decreases in trunk (1033.9 ± 528.6 %MVIC reduction in first hour) and gluteal cocontraction indices (398.8 ± 792.4 %MVIC decrease in the 15 minute block) and increases in the number of anterior-posterior centre of pressure fidgets (13.5 ± 25.4 increase in the 30 minute block) were observed in the first hour of the fatigue session in PDs. Female PDs had more posterior pelvic tilt with fatigue (3.9 ± 9.2° more posterior with fatigue from 30 to 90 minutes), distinguishing them from male PDs (7.0 ± 11.3° more anterior with fatigue from 15 to 120 minutes). Both pain groups had similar EMG frequency shifts and strength lost due to fatigue. NPDs had longer times to fatigue than PDs (NPDs: 20.1 ± 11.2 minutes; PDs: 18.7 ± 9.3 minutes; p = 0.0106). This study provides evidence that the hip abductor musculature is likely one causative factor in the low back pain developed from standing. Also, PDs had fatiguing characteristics of persons suffering from chronic low back pain, only without any pain present.
Keywords: Low Back Pain; Muscle Fatigue; Standing; Hip Abductor; Muscle Activity; Posture; Movement; Fatigue Recovery; Pain; Spine; Hip; Kinesiology